Morphology, polymorphism, and metal ion adsorption studies of electrospun nanofibers based on pvdf and organically modified layered double hydroxide - Birajdar, Mallinath S.; Wanjale, Santosh D.; Lonkar, Sunil P. (Journal of Applied Polymer Science, 2013)
Nonwoven nanofiber mats of polyvinylidene fluoride (PVDF) with modified layered double hydroxide (MLDH) were prepared by electrospinning. The fiber morphology was studied using scanning electron microscopy. X-ray diffraction and FTIR spectroscopy was used to characterize the polymorphism in electrospun mats. Fibers of diameter in the range 80-800 nm with beads of about 2-3 mu m size were observed for pure PVDF, while in case of PVDF/MLDH nanocomposites the number and size of beads were found to be significantly reduced. Uniform and fine nanofibers were obtained at lower content of MLDH, but slightly rough surface was seen for higher content. FTIR and X-ray diffraction patterns signify various crystalline forms of electrospun PVDF. The content of polar -crystalline phase of PVDF, which exhibit piezo and ferroelectric properties was found to be enhanced significantly due to reinforcement of MLDH. Use of these nanofiber mats for heavy metal Cu (II) removal was explored. (c) 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 130: 4508-4515, 2013
Keywords: Adsorption; electrospinning; fibers